Suggested techniques of unlocking vocabulary difficulties in reading selections for grades four, five, and six - Quimosing, Evelyn de la Cruz 1946- (1977)
Language is not an abstract construction of the learned, or of dictionary-makers, but it is something arising out of the work, needs, ties, joys, affections and tastes of many generations. Reading has always been referred to as a tool subject. Reading materials are the instruments for the cultivation of reading skills and habits. This paper dealt on vocabulary since the study of the structures peculiar to the language are provided for in the language phase. The focus of this paper is on unlocking of language difficulties brought about by the use of idioms, figurative language, prepositional phrases and words with multiply meanings.
"March, 1977."
Missing leaves 34-37, 155-159.
Vita.
Thesis (M.A.T. Reading)--University of the Philippines, Diliman.
Keywords: Vocabulary; Reading (Elementary) -- Philippines